PERFORMANCE TESTS OF PYROLISATORS WITH MULTIPLE CONDENSATION SYSTEMS - Kamal, Mustopa; Fachruddin, Faizal (Aurelia Journal, 2023)
Pyrolysator performance testing has been carried out on the results of liquid smoke produced by pyrolysators with a multilevel condensation system using coconut shell fumes. The parameters tested in the pyrolysator performance test were time, temperature, heating rate, volume of liquid smoke and residual combustion in the form of charcoal. Test results using Gas Chromatography-Mass Spectrophotometry (GC-MS) show that pyrolysators with multilevel condensation systems produce liquid smoke with food grade quality so it is safe to use as a natural preservative for fishery products. The amount of liquid smoke produced by the pyrolysator with a multilevel condensation system is 24% and charcoal is 46%, from the pyrolysis process of 10kg of coconut shells for 5 hours. It can be concluded that pyrolysators with multilevel condensation systems have advantages in terms of productivity when compared to conventional pyrolysators, so they are very suitable for use in the liquid smoke industry.